Concentration and Temperature Dependence of Shear Viscosity of the Critical Mixture of Nitroethane and 3-Methylpentane - Issam Abdelraziq (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
Shear viscosity coefficients of nitroethane and 3-methylpentane mixture have been measured using digital viscometer. The measured values were over the entire concentration range above the critical temperature (Tc = 299.590 K) in the range 0.040 ? T- Tc ? 18.570 K. The results above the critical temperature Tc were analyzed by the mode coupling theory. The anomaly of shear viscosity was detected as a function of temperature and concentration. A least square fit near the critical temperature yields a value of noncritical part of shear viscosity ?0 = 0.358 cP. The Debye momentum cutoff qD and the constant A in the mode coupling approach were determined. Our values of ?0 and A are in good agreement with the literature values.